The goals of EU competition law: a comprehensive empirical investigation. (December 2022) - Stylianou, Konstantinos; Iacovides, Marios
Abstract: For any field of law, the goal it was designed to achieve permeates every aspect of its application and interpretation. This is particularly true when the black letter of the law is cryptic and silent on most aspects of how it should be interpreted and applied, as is the case with competition law, which for the most part revolves around a small number of highly abstract provisions. It is only natural then that ample scholarly work has been devoted to identifying the goals and purposes of competition law. By and large these attempts have been textual, historical, and teleological. We introduce here instead a quantitative analysis of the case law and present the results of the first empirical study into the goals and purposes of EU competition law as they emerge from the entirety of the case law of the European Court of Justice, opinions of the Advocate Generals, Commission decisions, and speeches of Commissioners for Competition. This body of almost 4, 000 sources paints a comprehensive picture of the underlying goals of EU competition law, and helps conclusively confirm some previous insights while debunking others, thereby helping to advance the present application and future evolution of competition law.